Clocking molecular fragmentation of N2 with XUV pump-probe experiments - Zhang, Y. Zh; Senftleben, A.; Schnorr, K.; Schmid, G.; Kurka, M.; Rudenko, A.; Foucar, L.; Kübel, M.; Kling, M. F.; Ueda, K.; Treusch, R.; Ullrich, J.; et al. (My University, 2014)
The dynamics of multi-photon induced fragmentation of N2 has been investigated in XUV-pump/XUV-probe experiments at the Free-Electron Laser in Hamburg (FLASH) by recording the ion kinetic energy release(KER) and angular distributions for various dissociation- and Coulomb-explosion channels as a function of the pump-probe delay-time.